Perbandingan Respon Pertumbuhan dan Efisiensi Pakan Ikan Lele Sangkuriang (Clarias Gariepinus) Pada Berbagai Dosis Sinbiotik Berbasis Probiotik Rabal dan Ekstrak Ubi Jalar - Santri Purari Putra; Dedi Pardiansyah; Zulkhasyni; Reza Wahyuni; Mega Rahma Sari; Andi Komandala Pratama (University of Prof. Dr. Hazairin, SH, 2026)
The objective of this study was to evaluate the growth response, feed utilization efficiency, and survival rate of Sangkuriang catfish (Clarias gariepinus) that were fed diets supplemented with various doses of a synbiotic formulated from Rabal probiotics and sweet potato extract. The 60-day experiment used a completely randomized design (CRD) with three synbiotic dosage treatments: P1 (5%), P2 (10%), and P3 (15%), with four replicates per treatment. The study focused on comparing growth responses among synbiotic dosage levels and did not include a control treatment without synbiotic supplementation (P0). Therefore, the results could only be interpreted in terms of comparisons among the tested synbiotic doses. Observed parameters included weight gain, length gain, feed efficiency, feed conversion ratio (FCR), and survival rate. The results showed that different synbiotic doses produced significantly different growth responses (p < 0.01). The highest growth performance was obtained in the P3 treatment (15% synbiotic), resulting in the greatest weight (25.75 ± 0.20 g) and length (8.31 ± 0.02 cm) gains. Feed efficiency increased, reaching 0.80 in P3, while the FCR decreased to 1.29. However, the differences in feed efficiency and FCR among the treatments were not statistically significant (p > 0.05). The survival rate remained high, reaching 100% in all treatments. These findings suggest that higher synbiotic doses tend to produce better growth performance within the tested dosage levels while maintaining a high survival rate and comparable feed utilization efficiency in Sangkuriang catfish.